Factors influencing length of stay following cervical spine surgery: A comparison of myelopathy and radiculopathy patients. (September 2019) - Pierce, Katherine E.; Gerling, Michael C.; Bortz, Cole A.; Alas, Haddy; Brown, Avery E.; Woo, Dainn; Vasquez-Montes, Dennis; Ayres, Ethan W.; Diebo, Bassel G.; Maglaras, Constance; Janjua, M. Burhan; Buckland, Aaron J.; et al.
Highlights: Examined extended length of hospital stay in myelopathy, radiculopathy and myeloradiculopathy patients. 102 patients had extended length of stay, average: 5.96 days. Predictors of extended length of stay were explored for each diagnosis. Independent of invasiveness, patients with a diagnosis of myelopathy, had longer LOS. Abstract: In the current value-based healthcare climate where spine surgery is shifting to the ambulatory setting, factors influencing postop length of stay (LOS) are important to surgeons and hospital administrators. Pre-op patient factors including diagnosis of radiculopathy and myelopathy have yet to be investigated in this context. Operative pts ≥ 18Y with primary diagnoses of cervical myelopathy (M), radiculopathy (R), or myeloradiculopathy (MR) were included and propensity score matched by invasiveness score (Mirza et al.). Top-quartile LOS was defined as extended. M&R patients were compared using Chi 2 & independent t -tests. Univariate tests assessed differences in preop patient and surgical data in M&R pts and extended/non-extended LOS. Stepwise regression analysis explored factors predictive of LOS. 718 operative pts (54.5 yrs, 41.1%F, 29.1 kg/m 2, mean CCI 1.11) included (177 M, 383 R, and 158 MR). After PSM, 345 patients remained (115 in each diagnosis). 102 patients had E-LOS (Avg: 5.96 days), 41 M patients (mean 7.1 days), 28 R (5.9 days), and 33 MR (4.6 days). Regression showed predictors of E-LOS in R pts (R 2 = 0.532, p = 0.043): TS-CL, combined and posterior approach, LIV, UIV, op time, Lactated Ringer's, postoperative complications. Predictors of E-LOS in M pts (R 2 = 0.230, p < 0.001): age, CCI, combined and posterior approach, levels fused, UIV, EBL, neuro and any postop complications. Predictors of E-LOS in MR patients (R 2 = 0.152, p < 0.001): age, kyphosis, combined approach, UIV, LIV, levels fused, EBL and op time. Independent of invasiveness, patients with a primary diagnosis of myelopathy, though older aged and higher comorbidity profile, had consistently longer overall postop LOS when compared to radiculopathy or myeloradiculopathy patients.